2022
DOI: 10.1111/twec.13279
|View full text |Cite
|
Sign up to set email alerts
|

The trade impact of the COVID‐19 pandemic

Abstract: Using a gravity-like approach, we study how Covid-19 deaths and lockdown policies affected countries' imports from China during 2020. We find that a country's own Covid-19 deaths and lockdowns significantly reduced its imports from China, suggesting that the negative demand effects prevailed over the negative supply effects of the pandemic. On the other hand, Covid-19 deaths in the main trading partners of a country (excluding China) induces more imports from China, partially offsetting countries' own effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Baldwin (2020) pointed out that the pandemic might lead to a more severe trade recession than the outbreak of the global financial crisis in 2008–2009, as the pandemic is both a demand shock and a supply shock while the 2008–2009 recession was driven mostly by a demand shock. A similar and provocative study is by Liu et al (2021), also using the data on monthly year‐over‐year growth of China's trade. Liu et al (2021) find that the lockdown restrictions had affected imports more severely than the direct health and behavioural effects of the pandemic itself.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Baldwin (2020) pointed out that the pandemic might lead to a more severe trade recession than the outbreak of the global financial crisis in 2008–2009, as the pandemic is both a demand shock and a supply shock while the 2008–2009 recession was driven mostly by a demand shock. A similar and provocative study is by Liu et al (2021), also using the data on monthly year‐over‐year growth of China's trade. Liu et al (2021) find that the lockdown restrictions had affected imports more severely than the direct health and behavioural effects of the pandemic itself.…”
Section: Introductionmentioning
confidence: 92%
“…A similar and provocative study is by Liu et al (2021), also using the data on monthly year‐over‐year growth of China's trade. Liu et al (2021) find that the lockdown restrictions had affected imports more severely than the direct health and behavioural effects of the pandemic itself. This paper focuses on analysing and capturing changes in China's trade by using the same data and then offers some policy recommendations for China's future trade development.…”
Section: Introductionmentioning
confidence: 92%
“…Related literature. Our paper contributes to a burgeoning literature on the propagation of the COVID-19 pandemic shock through global trade (e.g., Bonadio et al, 2021;Espitia et al, 2022;Lafrogne-Joussier et al, 2022;Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…The COVID-19 pandemic constituted both a demand and a supply shock and the twin nature of the shock was expected to lead to a sharp decline in trade (Baldwin and Tomiura, 2020;Buchel et al, 2020;Liu et al, 2022). For an economy experiencing COVID-19, the economic contraction resulting from domestic pandemic containment policies, such as restrictions on mobility (and social distancing), was expected to lead to a large contraction in demand, and thus a decline in imports.…”
Section: Introductionmentioning
confidence: 99%
“…Büchel et al (2020) focused on Switzerland and found that the country's trade decline depends mainly on domestic and foreign demand shocks. Similarly, Liu et al (2021) concluded that negative demand effects in both dimensions (direct and indirect effects of the pandemic and response measures) predominate when using year‐over‐year monthly growth in imports from China at the HS 6‐digit product level. Another strand of the relevant literature examines the transmission function of GVCs from the perspective of their impact on real economic activity and prices (Meier & Pinto, 2020), output adjustments to cross‐sectoral effects of labour supply shocks (Bonadio et al, 2020; McCann & Myers, 2020), and aggregate welfare, through both deaths and reduced gains from trade (Antras et al, 2020).…”
Section: Introductionmentioning
confidence: 99%